The roles and outcomes of surgery in large anterior mediastinal tumors - Yan Le Ho; Mohammad Fauzi bin Jamaluddin; Gerard Francis Lopez; Sotheenathan Krishinan; Abu Yamin bin Khamis; Basheer Ahamed bin Abdul Kareem (The Journal of Association of Chest Physicians)
Introduction: Large anterior mediastinal tumors are rare and encompass a wide diversity of neoplasms. The anatomical complexity of large mediastinal tumors poses clinical challenges in term of surgical feasibility, tumor resectability, and disease curability. Due to the rarity of this clinical entity, very few studies have been conducted on large mediastinal tumors. Here, we describe the surgical approach and outcomes of surgery for large mediastinal tumors. Method: A retrospective analysis was conducted on patients with large anterior mediastinal tumors who underwent biopsy and surgical resection at our center from January 2018 to December 2020. Results: A total of 87 patients were referred for anterior mediastinal tumors, and 42 of them (48.3%) had tumors larger than 8 cm. The average age was 36.4 years, with a male-to-female ratio of 4:6. The average tumor size was 13.2 cm. Twenty-six patients (61.9%) underwent surgical biopsy; 16 of them were diagnosed with lymphoma, and another 10 patients had nonlymphoma tumors. Complete surgical resection was performed on 24 patients (57.1%). Surgical biopsies were performed using video-assisted thoracoscopic surgery (61.5 %) and the Chamberlain procedure (38.5%). Surgical resection was performed with median sternotomy (66.7%), thoracotomy (20.8%), and hemiclamshell approach (12.5%). There were no immediate postoperative mortality. Conclusion: This series has shown the clinical feasibility of definitive surgical management for large mediastinal tumors, with positive clinical outcomes. Given the rarity of large mediastinal tumors, detailed preoperative preparation with multimodal imaging and multidisciplinary team discussion are essential for favorable surgical outcomes.